ANALISIS KONDISI BONDING ANTAR LAPISAN BERASPAL SECARA TEORITIS DAN PENGUJIAN DI LABORATORIUM - Eri Susanto Hariyadi; Bambang Ismanto Siswosoebrotho; Djunaedi Kosasih; Bambang Sugeng Subagio (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2007)
Abstract The condition of bonding between asphalt pavement layer can influence the behaviour of pavement structure in supporting vehicle loading. In strong bonding condition, the adjacent pavement layers will act together to support pavement loading and the other way in weak bonding condition the layers will act independently with the result that stress in every layer of pavement become higher and will decrease pavement life consequently. This study described the investigation of bonding condition using teorethical model and laboratory test. Those are developed using CIRCLY5-SAP2000 Program and Modified Direct Shear Test respectively. The results shown that there is the range of bonding parameter which starting from weak bonding until full bonding using theoretical and laboratory model. Futhermore the analysis shown that ignoring bonding condition between pavement layer will become one of factors which cause early damage in pavement structure.Keywords : Bonding, Direct Shear Test, SAP2000, CIRCLY5